Influence of the amphibious transporter STM – M on environment - Kovačević, Nenad V. (Vojnotehnički glasnik / Military Technical Courier, 2013)
The Serbian Army is the only institution of the social system in the Republic of Serbia which posesses amphibious vehicles and uses them for their designated purpose. The goal of this paper is to draw conclusions regarding the influence of amphibious vehicles on the three parts of the environment many scientists find the most important: land, air and water. The paper processes the influence of amphibious military vehicles on the basic parts of environment, as well as the measures for the improvement of safety and environmental management systems regarding the change in the usage and reconstruction of the vehicles. This paper is based on the authors’ own experience in work with amphibious vehicles combined with the basic theoretical postulates of the safety and environmental management sistems. It also shows how many negative consequences on the environment can be caused by just one type of the military vehicles. It is very important to emphasize that this paper does not include all negative influences of amphibious vehicles on the environment, since it is based on the negative influence of amphibiuos vehicles on the basic indicators of environment only. Introduction Some basic information about environment pollutionis given here as well as Figure 1 with some basic types of pollutioncaused by Armed Forces. Development of amphibious vehicles in foreign Armed Forces This short historical review of all amphibious vehicles in the worldand their origins is illustrated with some of their past and future examples. Development of amphibious vehicles in the Serbian Armed Forces Besides some basic facts about amphibious vehicles in the Serbian Armed Forces, the paper concentrateson the amphibious transporter STM – M. Its tactical and technical specifications are given and its looks can be seen in Figure 5. Influence of the amphibious transporter STM – M on environment The advantages and disadvantages of using the transporterare discussed as well as the influences of the transporter on the basic elements of environment – land, air and water. Some measures for improving the usage of the transporter are proposed. One example of the harmful consequences of its wrong maintenance and use is presented in Figure 6. A certain modification of the transporter, involving minimal financial resources, has been proposed. Conclusion After giving some facts about the transporter non-designated usage and its maintenance, the conclusion focuses on a proposed solution for making transporters more useful and less harmful for the environment.
Keywords: Serbian Armed Forces; Environmental Engineering; amphibious vehicles